Metabolic Effects of Eicosapentaenoic Acid in the APPswePS1dE9 Alzheimer's Mouse Model. (29th May 2020) - Yavari, Mahsa; Ramalingam, Latha; Harris, Breanna; Scoggin, Shane; Biltz, Caroline; Chavira, Angela; Mounce, Logan; Maldonado, Kaylee Alers; Moustaid-Moussa, Naima
Abstract: Objectives: Alzheimer's disease (AD) is a neurodegenerative disorder, characterized by presence of amyloid plaques. Exact etiology treatment and early diagnosis is still unknown and not possible. Obesity is an important risk factor of neurodegenerative disorders. Eicosapentaenoic acid (EPA), a long-chain omega-3 polyunsaturated fatty acid exerts anti-inflammatory effects, but how EPA affects AD is unknown. This study aims to determine whether EPA supplementation improves overall metabolic status in transgenic APPswePS1E9 mouse model. Methods: Mice were sexed, transgenic (Tg) and wild type (Wt), randomly assigned at 2 months of age to a diet treatment: low fat (LF), high fat (HF), or high fat with EPA (HF-EPA), with 10–12 mice per diet for each sex and genotype. Weekly, body weight (BW) and food intake were recorded. Body composition (BC) conducted every 2 months and glucose tolerance tests were conducted at 5 months. At 10 months, mice were euthanized, and tissues and serum were collected. Results: Differences in BW among groups were observed from 8 months and results differed by sex and genotype ( P < 0.05). In male mice, diet did not affect BW in Wt group, but Tg males fed HF had significantly higher BW than LF Tg, with no difference between HF and HF-EPA. Among female mice, HF groups (HF or HF-EPA) in both genotypes were significantly heavier than those fed LF, while HF and HF-EPA did not differ. Fat mass measured during the 4th and 6th month in males was significantly higher in all HF groups compared to LF genotypes. However, at 10th month, fat mass was higher only in HF mice of both genotypes in comparison with LF, with no difference between HF or HF-EPA groups. In females, only HF-EPA fed mice had higher fat mass than LF genotypes at 10 months. In males, no difference was observed in glucose clearance among Wt mice, regardless of the diet. However, only male HF-Tg mice had lower glucose clearance compared to LF genotypes, while HF and HF-EPA were comparable. In females, HF-EPA Tg mice had lower glucose clearance compared to LF and HF Tg mice. Conclusions: These findings indicate that HF diet induced sex-independent metabolic dysfunction in both Wt and Tg mice. However, EPA did not exert any metabolic effects based on BW, glucose tolerance and adiposity. Further tissue-specific analyses are ongoing to understand the basis for these diet, sex and genotype differences. Funding Sources: NIH (NCCIH and NIA).